Cognitive behavioral therapy (CBT) - Touch Mercer, Gina (Henry Stewart Talks, 2022)
Cognitive behavioral therapy (CBT), Evidence-based psychotherapy, Behavioral science, Clinical psychology, Addressing core beliefs in CBT, Insomnia, anxiety and depression, CBT and the mind-body connection, Patient-centered care, Patient counseling